Returning to Work After Sick Leave – The Role of Work Demands and Resources, Self-Efficacy, and Social Support - Boštjančič, Eva; Galič, Kaja (Frontiers in Psychology, 2020)
Returning to work after sick leave is a process that begins with the initial steps of functional recovery and results in full vocational capacity. Different personal and situational factors could influence an employee’s well-being after returning. The following research was conducted in order to examine how occupational demands and resources, self-efficacy, and social engagement contribute to the return-to-work process. A total of 256 employees took part in the study, who were later divided into two groups: short- (less than 30 days), and long-term (more than 30 days) sick leave. We measured their self-efficacy at the workplace, recent job demands and resources, social engagement, and work satisfaction after returning to work after sick leave. The results showed that personal (gender, age, self-efficacy), social (social engagement), and occupational (job demands and resources) factors are associated with the duration of sick leave. Participants who were on shorter sick leaves reported being more satisfied with their work after returning than those returning from long-term sick leave. The research presents important insights that could help employers better understand the needs of employees who are returning to work after sick leave.